Tiempo, recuerdo, memoria y onirismo en "Lo raro es vivir" - Barrera García, Consuelo (Huarte de San Juan. Filología y Didáctica de la Lengua, 1997)
This study analyses, the latest novel by Carmen Martín Gaite "Lo raro es vivir”. The book tackles the narrator-protagonist’s psychological time. Recollections,memory and oneirism in such a way that it is impossible to define the limits of her true reality, her memories or her dreams. The characters are sketched well enough to frame their personality nature and their function in the novel and it especially focus on their problems.